2022
DOI: 10.4102/sajpsychiatry.v28i0.1779
|View full text |Cite
|
Sign up to set email alerts
|

Depression and quality of life among pregnant women in first and third trimesters in Abeokuta: A comparative study

Abstract: Background: Pregnancy is a dynamic time during which a woman’s emotional state may undergo extensive change. There have been conflicting views about the magnitude of emotional turmoil that occurs during pregnancy. Some investigators suggest that pregnancy is a time of particularly good psychological adjustment; others have reported high levels of psychological challenge.Aim: Our study aimed to compare the prevalence and correlates of depression in the first and third trimesters of pregnancy and to determine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 60 publications
(70 reference statements)
1
4
0
1
Order By: Relevance
“…There have been differing opinions on the extent of emotional anguish during pregnancy. In addition, pregnancy is a period of perfect psychological adjustment, whereas others report significant levels of psychological strain (Soyemi et al, 2022). The results showed that most respondents were aged 20-35.…”
Section: Characteristics Of Respondentsmentioning
confidence: 97%
See 2 more Smart Citations
“…There have been differing opinions on the extent of emotional anguish during pregnancy. In addition, pregnancy is a period of perfect psychological adjustment, whereas others report significant levels of psychological strain (Soyemi et al, 2022). The results showed that most respondents were aged 20-35.…”
Section: Characteristics Of Respondentsmentioning
confidence: 97%
“…This could be explained by the fact that these are prior adverse life events, and the dread of a repeat, particularly as the pregnant lady begins to accept the pregnancy, may cause depressive disorder. Having more than two children, particularly with the related financial strain, may cause persistent concern linked with negative thoughts, triggering depressive symptoms (Soyemi et al, 2022).…”
Section: Characteristics Of Respondentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Menurut Soyemi, Sowunmi, Amosu, dan Babalola (2022) ibu dengan paritas multigravida dan kehamilan yang tidak direncanakan terutama yang memiliki masalah terkait ekonomi menjadi sumber kekhawatiran, pikiran negatif yang terus-menerus dan kemudian memicu gejala depresi. Ibu hamil dengan depresi memiliki kepuasan yang lebih rendah terhadap kualitas hidup mereka, hal ini dikarenakan ibu hamil dengan depresi cenderung memiliki pandangan negatif dan tidak rasional terhadap diri mereka sendiri, masa depan, dan lingkungan di sekitar mereka begitupula sebaliknya (Soyemi, Sowunmi, Amosu, & Babalola 2022). Penelitian yang dilakukan Bo et al (2021) di Tiongkok menyatakan bahwa ibu hamil dengan gejala depresi memiliki kualitas hidup lebih rendah dibandingkan ibu hamil tanpa gejala depresi.…”
Section: Hubungan Depresi Dan Kualitas Hidupunclassified
“…It is also known that a depressive episode negatively impacts the Quality of life (QoL), characterized by a global well-being and the ability in carrying out the tasks of living (Hohls et al 2021). The impact of GD on women's Quality of Life remains a neglected matter of study, mainly in low-or middle-income countries (Soyemi et al 2022).…”
Section: Introductionmentioning
confidence: 99%